Biofilm formation, antibiotic susceptibility and RAPD genotypes in Pseudomonas aeruginosa clinical strains isolated from single centre intensive care unit patients - Vaněrková, Martina; Mališová, Barbora; Kotásková, Iva; Holá, Veronika; Růžička, Filip; Freiberger, Tomáš (Folia microbiologica, 2017)
The aim of this study was to analyse genotypes, antimicrobial susceptibility patterns and serotypes in Pseudomonas aeruginosa clinical strains, including the clonal dissemination of particular strains throughout various intensive care units in one medical centre. Using random amplified polymorphic DNA (RAPD-PCR) and P. aeruginosa antisera, 22 different genotypes and 8 serotypes were defined among 103 isolates from 48 patients. No direct association between P. aeruginosa strain genotypes and serotypes was observed. RAPD typing in strains with the same serotype revealed different genotypes and, on the contrary, most strains with a different serotype displayed the same amplification pattern. The resulting banding patterns showed a high degree of genetic heterogeneity among all isolates from the patients examined, suggesting a non-clonal relationship between isolates from these patients. A higher degree of antibiotic resistance and stronger biofilm production in common genotypes compared to rare ones and genetic homogeneity of the most resistant strains indicated the role of antibiotic pressure in acquiring resistant and more virulent strains in our hospital. In conclusion, genetic characterisation of P. aeruginosa strains using RAPD method was shown to be more accurate in epidemiological analyses than phenotyping.
Keywords: Microbial Sensitivity Tests; technika náhodné amplifikace polymorfní DNA; Humans; lidé středního věku; Random Amplified Polymorphic DNA Technique; Antibiotic Susceptibility; Meropenem; Female; Aged; mladý dospělý; dospělí; mikrobiální testy citlivosti; senioři; lidé; Genotype; antibakteriální látky; Pseudomonas aeruginosa; Adult; Common Genotype; Pseudomonas Infections; Antimicrobial Susceptibility Pattern; ženské pohlaví; Anti-Bacterial Agents; Male; biofilmy; jednotky intenzivní péče; Middle Aged; Drug Resistance, Bacterial; Unique Genotype; Aged, 80 and over; Young Adult; senioři nad 80 let; bakteriální léková rezistence; genotyp; Intensive Care Units; mužské pohlaví; pseudomonádové infekce; Biofilms